2019
DOI: 10.1111/josi.12350
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Racism: A Systematic Review of the Psychological Literature on Racism's Most Insidious Consequence

Abstract: Racism is often thought of as existing and operating at the interpersonal and institutional levels. One aspect of racism that has been relatively forgotten, however, is its internalized component: racism that exists and operates at the internalized level. Surprisingly, even psychology—the field that is arguably best equipped to study the internalized component of racism—seems to have lagged in investigating and addressing this construct. Thus, we conducted a systematic literature review of psychological work o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(168 citation statements)
references
References 111 publications
4
162
0
2
Order By: Relevance
“…Less research has brought in-as we did in the current study-additional social identities that perceivers might hold beyond those targeted by the stereotypes under investigation (e.g., the stereotypes that White participants vs. participants of color have about men and women). Although gender stereotypes are widely endorsed (e.g., Glick et al, 2000;Williams & Best, 1990), there is also some evidence that perceivers' race matters (e.g., Dugger, 1988;Nosek et al, 2007;O'Brien et al, 2015; see also David, Schroeder, & Fernandez, 2019). For example, O'Brien et al (2015) found that Black women were less likely than White women to implicitly associate STEM with men (see also Evans, Copping, Rowley, & Kurtz-Costes, 2011), and these implicit stereotype differences predicted Black women's greater likelihood of majoring in STEM fields relative to White women.…”
Section: The Potential Role Of Perceivers' Racementioning
confidence: 99%
See 1 more Smart Citation
“…Less research has brought in-as we did in the current study-additional social identities that perceivers might hold beyond those targeted by the stereotypes under investigation (e.g., the stereotypes that White participants vs. participants of color have about men and women). Although gender stereotypes are widely endorsed (e.g., Glick et al, 2000;Williams & Best, 1990), there is also some evidence that perceivers' race matters (e.g., Dugger, 1988;Nosek et al, 2007;O'Brien et al, 2015; see also David, Schroeder, & Fernandez, 2019). For example, O'Brien et al (2015) found that Black women were less likely than White women to implicitly associate STEM with men (see also Evans, Copping, Rowley, & Kurtz-Costes, 2011), and these implicit stereotype differences predicted Black women's greater likelihood of majoring in STEM fields relative to White women.…”
Section: The Potential Role Of Perceivers' Racementioning
confidence: 99%
“…Less research has brought in—as we did in the current study—additional social identities that perceivers might hold beyond those targeted by the stereotypes under investigation (e.g., the stereotypes that White participants vs. participants of color have about men and women). Although gender stereotypes are widely endorsed (e.g., Glick et al., ; Williams & Best, ), there is also some evidence that perceivers’ race matters (e.g., Dugger, ; Nosek et al., ; O'Brien et al., ; see also David, Schroeder, & Fernandez, ). For example, O'Brien et al.…”
Section: Prior Evidence On the Early Acquisition Of The Gender‐brillimentioning
confidence: 99%
“…Specifically, publications in these journals commonly include samples from racial and ethnic minorities, which can assist researchers in developing theoretically informed hypotheses that do not simply anchor on research findings from racial majority populations. For example, this issue of the Journal of Social Issues includes articles with racially and ethnically diverse participant samples (Albuja, Gaither, Sanchez, Straka, & Cipollina, 2019;Castillo-Lavergne & Destin, 2019;Jaxon, Lei, Shachnai, Chestnut, & Cimpian, 2019) or articles that review research examining mostly racial and ethnic minority individuals (David, Schroeder, & Fernandez, 2019;Ozier, Taylor, & Murphy, 2019). The authors of these papers also reflect racially and ethnically diverse research teams.…”
Section: Implementing the Proposed Guidelinesmentioning
confidence: 99%
“…Internalized racism is conceptualized as the product of systems of privilege and societal values that, over time, erode an individual's sense of value and undermine the collective action of a minority racial and/or ethnic group (Jones, 2000). Scholars argue that internalized racism represents a multidimensional construct, distinct from racial discrimination (e.g., Bailey et al, 2011;David et al, 2019), that includes: belief in a biased representation of history (acceptance of distorted historical facts that favor the White majority; Clarke, 1991), internalization of negative stereotypes (accepting the negative stereotypes about African Americans; Cokley, 2002), and alteration of physical appearance (an individual's conscious or unconscious desire or attempts to change their appearance to fit a Eurocentric aesthetic including perceptions of hair; Parmer et al, 2004). Clark and colleagues' (1999) biopsychosocial model of racism posits that racism results in psychological and physiological stress responses that can be linked to negative psychological wellbeing, and Jones ' (2000) model categorizes internalized racism as a stressor for African Americans.…”
mentioning
confidence: 99%